Smart Green Technology and Sustainability Training for Competency Alignment and Transformation for UM Alumni - Viola Malta Ramadhani; Riana Nurmalasari; Kintan Desinta (International Journal of Education, Information Technology, and Others, 2026)
The rapid development of smart technology demands the adjustment of human resource competencies in various technological, business, and industrial sectors. However, field observations revealed that Universitas Negeri Malang (UM) alumni, both entrepreneurs and employees in engineering fields, experienced competency gaps because smart technology material and sustainability principles had not been comprehensively accommodated in the previous curriculum. This activity aimed to align competencies and facilitate sustainable digital transformation for UM alumni through training and mentoring in Smart Green Technology and Sustainability. The activity was carried out through an interactive project-based approach divided into six effective face-to-face meetings. The methods applied included in-depth needs analysis, delivery of theoretical materials, programming and hardware installation workshops, and analysis of environmentally friendly technology implementation in the participants' business units. The results of this community service activity showed significant improvements in technological literacy, practical skills, and awareness of energy efficiency and environmental sustainability among alumni. The pre-test and post-test assessments recorded an average increase in technical understanding of 48.5%, with 70% of participating entrepreneurial alumni successfully designing an initial prototype for integrating an IoT-based monitoring system into their business units. This activity demonstrates that collaborative synergy between universities and alumni can bridge the barrier of high external training costs while accelerating UM alumni's progress in remaining competitive, adaptive, and environmentally conscious amid the rapid dynamics of the digital era